ANALISIS PENGARUH TATO, WCTO, DAN DER TERHADAP NILAI PERUSAHAAN DENGAN ROA SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2009-2013) - Utami, Rahmawati Budi; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2016)
The aims of this research is to examine the direct effect and indirect effect of Total Asset Turnover, Working Capital Turnover, Debt to Equity Ratio on Firm Value with Return On Asset as an intervening variable.This research sample is manufacturing companies listed in the Indonesia Stock Exchange (IDX) period 2009-2013 by using purposive sampling method. There are 64 manufacturing companies selected as sample. The method of analysis used is Path Analysis, the development of multiple linear regression.Using multiple regression analysis, it is known that TATO has positive significant effect on ROA. WCTO and DER has negative significant effect on ROA. TATO has positive not significant effect on Firm Value. WCTO has negative significant effect on Firm Value. DER and ROA has positive significant effect on Firm Value. The result of path analysis showed that TATO influence Firm Value through ROA. Besides, it was found that the value of the adjusted R square for the equation ROA is 25,3% while the value of the adjusted R square for the equation PBV is 39,7%.